Integrasi program TPQ dalam pembelajaran formal untuk meningkatkan literasi Al-Quran Siswa - Shima, Inara; Fathur Rohman (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2025)
This study aims to describe the integration of the flagship program of the Al-Quran Education Park (TPQ) and analyze its impact on students’ ability to read the Qur’an at MI As-Salam Kancilan Jepara. The study is motivated by the low level of Quranic literacy, primarily due to limited access to TPQ outside of school. A descriptive qualitative approach was employed, with data collected through observation, interviews, and documentation. The results indicate that the TPQ program is implemented through student needs-based planning, daily morning sessions using the Yanbu’a method, and tiered evaluations via achievement books and IMTAS assessments. The program significantly enhances students’ Qur’anic reading skills in terms of fluency, tajwid, and articulation. Additionally, the integration fosters an emotional and spiritual connection to the Qur’an among students. This study recommends the TPQ integration model as a viable solution for elementary educational institutions to enhance students' holistic religious literacy. The findings also imply opportunities for future research focusing on character development, digital approaches, and the effectiveness of implementation in other school contexts.